Evaluating Accommodation and Infrastructure for Sustainable Eco-Tourism Development in Mangrove Forest Destinations - Wahyuni, Vini; Rahman, Abdu; Apriani, Hilda (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
The study aims to explore the crucial role of courses on Sanitation, Hygiene, and Safety in enhancing the standards of the food and beverage industry in Soppeng Regency. The methodology involves conducting surveys among food business operators and analyzing emic data to evaluate their knowledge of hygiene, sanitation, and safety practices. Findings reveal that many operators have limited awareness of food spoilage caused by microorganisms, and they receive insufficient training on maintaining workplace safety standards. This knowledge gap potentially undermines product quality and poses significant health risks to consumers. Additionally, the study identifies a lack of standardized guidelines for sanitation and safety that are consistently adhered to across the industry. The conclusion highlights the importance of continuous education and comprehensive training programs aimed at improving operators' knowledge of hygiene and sanitation, thereby addressing these shortcomings. Strengthening this understanding is crucial for supporting sustainable tourism, enhancing consumer confidence, and elevating overall service standards within the food and beverage sector in Soppeng Regency, fostering a safer and more appealing industry environment.